Fair Value Measurement, 3rd Edition - Zyla, Mark (Wiley corporate F & A, 2020)
Get up to date on the latest FASB, SEC, and AICPA guidelines and best practices Fair Value Measurement provides hands-on guidance and the latest best practices for measuring fair value in financial reporting. The Financial Accounting Standards Board (FASB), the U.S. Securities and Exchange Commission (SEC), and the American Institute of CPAs (AICPA) have all updated their guidelines for practitioners, and this book details the changes from a practical perspective. This new third edition includes a discussion on Private Company Council accounting alternatives for business combinations and impairment testing, with a detailed example of the Market Participant Acquisition Premium (MPAP), including European and Asian examples and expanded discussion of IFRS. Fair value measurement guidelines continue to evolve, and this comprehensive reference provides a valuable, up-to-date resource for preparers, auditors, and valuation specialists. Adopt the best practices for implementing the FASB's Topic 820 Learn the latest reporting requirements for fair value measurements Understand accounting alternatives for business combinations Examine the details of MPAP in Europe and Asia Applying fair value measurements to financial statements requires a move away from rules-based standards and toward application of professional judgment. This controversial shift has led to a reliance on valuation specialists, who face their own challenges in applying Topic 820 amidst an economic downturn and recovery, leading to an ever evolving set of best practices. Practitioners must stay up to date, and be aware of the changes as they occur. Fair Value Measurement provides the most recent information and a practical approach to this area of financial reporting.